2010
DOI: 10.3109/03009730903573253
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 17β-oestradiol and norethisterone acetate on sulfonation and sialylation of gonadotrophins in post-menopausal women

Abstract: BackgroundThe number of terminal sialic acid and sulfonated N-acetylgalactosamine (SO3-GalNAc) on gonadotrophins in serum varies during the menstrual cycle and changes at menopause, suggesting that gonadal steroids modify their oligosaccharide synthesis. Our objective was to determine the effects of 17β-oestradiol (E2) and a progestogen, norethisterone acetate (NETA), on the sulfonation and sialylation of gonadotrophins in post-menopausal women.MethodsSerum samples were obtained from eight post-menopausal wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The progestin+EE treatment decreased the mean levels of FSHtri, FSHtetra, and LHtri compared with the mean values of the follicular phase and decreased the sialylation of FSHtri. The decreased sialylation of FSH by the EE treatment is in agreement with previously observed effects of 17β-estradiol in postmenopausal women [ 31 ]. The low degree of sialylation of FSHtri molecules during the 28-day treatment cycle is expected to contribute to the low mean serum level of the FSHtri glycoform during this treatment.…”
Section: Discussionsupporting
confidence: 91%
“…The progestin+EE treatment decreased the mean levels of FSHtri, FSHtetra, and LHtri compared with the mean values of the follicular phase and decreased the sialylation of FSHtri. The decreased sialylation of FSH by the EE treatment is in agreement with previously observed effects of 17β-estradiol in postmenopausal women [ 31 ]. The low degree of sialylation of FSHtri molecules during the 28-day treatment cycle is expected to contribute to the low mean serum level of the FSHtri glycoform during this treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Administration of 17β-oestradiol and progestogen preparations to postmenopausal women has been shown to change the contents of SA and SU residues per molecule on both FSH and LH in serum (40). This suggested steroid effects on the enzymes in the trans-Golgi of the pituitary gonadotrophin-producing cells.…”
Section: Discussionmentioning
confidence: 99%
“…29 Recent studies have shown that estradiol administered to postmenopausal women shifts pituitary FSH release to more basic FSH isoforms compared with non-treated women. 28 Thus, in addition to the fine-tuned interplay between the selected developing follicle and pituitary release of gonadotrophins, it appears that the follicle is capable also of directing the isoform profile released.…”
Section: Natural Fsh Isoforms and Their Physiological Relevancementioning
confidence: 99%
“…The selected follicle vastly increases its capacity to produce estradiol; shortly after selection, .90% of the estradiol present in the body is derived from this follicle. 28 Recent evidence suggests that the estradiol secreted by this follicle plays an important role in directing the pituitary output of FSH isoforms. 28 Pituitary expression of different glycosyl transferases, including 2,3 α-sialyltransferase (an enzyme that catalyses the incorporation of sialic acid residues into sugar residues attached to the FSH molecule), is down-regulated by estradiol.…”
Section: Natural Fsh Isoforms and Their Physiological Relevancementioning
confidence: 99%
See 1 more Smart Citation